KEPEMIMPINAN TRANSFORMASIONAL, KOMUNIKASI INTERPESONAL, LINGKUNGAN KERJA NON FISIK DAN KINERJA PEGAWAI DINAS PERUMAHAN DAN KAWASAN PERMUKIMAN KABUPATEN KARANGASEM - Ni Luh Sili Antari; Ni Luh Suarmini (Journal of Applied Management Studies, 2022)
In a government organization, success or failure in carrying out tasks and administering government is influenced by leadership, through leadership and supported by adequate government organizational capacity, the implementation of good governance will be more easily realized. In addition to leadership, another thing that is no less important in running the organization's wheels in government agencies is communication. Communication at the Department of Housing and Settlement Areas of Karangasem Regency is in the form of coordination and consultation regarding the duties and authorities of the agency. Communication with a personal approach needs to be done, to foster employee morale, in order to achieve the expected performance targets. The work environment is also very influential on performance in addition to leadership and communication above. The Department of Housing and Settlement Areas of Karangasem Regency is one of the government agencies in Karangasem Regency that is required to always provide friendly and good service to the people of Karangasem Regency. Therefore, employees of the Department of Housing and Settlement Areas of Karangasem Regency are required to have good performance as a benchmark for assessment from superiors. The sample in this study were 48 employees at the Department of Housing and Settlement Areas of Karangasem Regency. The determination of the number of samples used by the author in this study is by the census method based on the provisions put forward by Sugiyono (2002: 61-63), which says that: "Sample sampling is a sampling technique when all members of the population are used as samples. Another term for saturated sample is census. The analysis used is multiple linear regression analysis. The results of this study indicate that the variables of transformational leadership, interpersonal communication and non-physical work environment partially affect the performance of employees at the Department of Housing and Settlement Areas of Karangasem Regency.